Keefektifan Konseling Rational Emotive Behaviour Teknik Cognitive Disputation untuk Mengurangi Tingkat Fanatisme terhadap Idola pada Siswa Penggemar K-Pop - Nandita Aprilias; Bambang Dibyo Wiyono (Universitas Kanjuruhan Malang, 2019)
Behavior of K-Pop fans in grade science 3 of State Boarding Aliyah 2 Gresik, leads to behaviour of fanaical fans. The purpose of this research is to know the effectiveness of rational emotive behavior counseling with a pre-test post- test one group design. The instrument of this research is questionnaire of idol fanatiscm for K-Pop fans. The subject of this research is 3 K-Pop fans students from grade science 3 who have a high level of fanatiscm, based on the pre-test result. Analysis technique that used in this research is paired sample t test. Based on calculation, obtained Asmp. Sig (2 tailed) = 0,015. According to the basic of decision, accepted if Asmp. Sig (2 tailed) < 0,05. Because of Asmp. Sig 0, 015 < 0,05, the accepted, and that means there is a difference between before and after of rational emotive behavior counseling implementation. So, it can be concluded that counseling rational emotive behavior with cognitive disputation technique is effective for reduce idol fanaticism of K-Pop fans students.